Alternative Agents to Colcemid for Obtaining High-Quality Metaphase Spreads - Michele Zannotti; Marco Battelli; Pietro Parma (Animals)
In cytogenetics, the ability to perform FISH (Fluorescence In Situ Hybridization) experiments using probes that map very closely together depends on the capacity to produce sufficiently long chromosomes. Traditionally, colcemid is the chemical agent used to obtain metaphase spreads. However, various substances have been reported to arrest cells in an earlier stage of mitosis than the metaphase, potentially providing longer chromosomes. In this study, we tested seven substances different from colcemid, which, according to the literature, have this capability: Vinblastine, Combretastatin A-4, Podophyllotoxin, Org9935, Nocodazole, Paclitaxel, and Griseofulvin. All substances were tested on lymphocyte cultures derived from whole blood at the same concentration: 0.1 µg/mL. Among these, Org9935 and Griseofulvin were confirmed to have the ability to produce metaphases with longer chromosomes compared to those obtained with colcemid.